2015
DOI: 10.7763/ijmo.2015.v5.449
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Conventional CUSUM Control Chart for Correlated Observations

Abstract: Abstract-Control charts, one of the important tools of quality control, are also known as Shewhart charts or process behavior charts. Page (1954) was the first, who introduced the Cumulative Sum (CUSUM) control charts for detection of process shifts and claimed that these charts are more efficient compared to Shewhart chart to detect small shifts in the process average. Various schemes of the CUSUM chart for autocorrelated data for sample size of 4 are developed and compared with the schemes of the Shewhart X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Therefore, the shift size is not anticipated in this analysis for detecting the shift in the precipitation variability in SSA and CNC. The control limits for the tabular routine (Prajapati 2015)…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the shift size is not anticipated in this analysis for detecting the shift in the precipitation variability in SSA and CNC. The control limits for the tabular routine (Prajapati 2015)…”
Section: Methodsmentioning
confidence: 99%
“…Change point analysis finds the significant break point at which there is a significant change in risk, which indicates the potential need for a mitigation decision. A process control technique, such as a cumulative sum (CUSUM) control chart, is used to determine the break point . The CUSUM of each score is “calculated by adding the difference between the current value and mean to the previous sum,” as shown in Equation : Si=Si1+false(XiX¯false)fori=1ton,where S is the CUSUM, Xi is the current value, and X¯ is the mean.…”
Section: Methodsmentioning
confidence: 99%
“…The final step is to calculate the relative closeness to the ideal solution of each evaluation factor using Equation (10): to determine the break point. 50,51 The CUSUM of each score is "calculated by adding the difference between the current value and mean to the previous sum," as shown in Equation (11): 52…”
Section: Literature Reviewmentioning
confidence: 99%
“…These control charts are well known for detecting SPC problems. More detection methods for small process shifts have been suggested by Yashchin [4], Zhang [5], Psarakis and Papaleonida [6], Prajapati [7], and Mawonike and Nkomo [8]. They have shown that the CUSUM and EWMA control charts are more effective than the Shewhart control chart for monitoring small changes and for autocorrelated processes.…”
Section: Introductionmentioning
confidence: 99%